Levels and change in autonomous and controlled work motivation in older workers—The role of proximity to retirement and sense of community at work. Issue 1 (22nd October 2022) - Henning, Georg; Stenling, Andreas; Tafvelin, Susanne; Ebener, Melanie; Lindwall, Magnus
Abstract: Previous studies suggest a preretirement disengagement process from work, which includes reduced work motivation. In this study, we investigated changes in autonomous and controlled work motivation over two years among participants of the Health, Aging and Retirement Transition in Sweden (HEARTS) study. We found stability in both types of motivation; however, those who retired after the study period showed more distinct declines in autonomous motivation. A stronger sense of community at work was related to level, but not change in autonomous motivation. Intra‐individual fluctuations in the expected retirement age did not predict work motivation or vice versa. Future studies are needed to better understand the antecedents and consequences of preretirement declines in autonomous work motivation.